INOVASI SENAM HAMIL BERBASIS KOMUNITAS SEBAGAI UPAYA MEWUJUDKAN KEHAMILAN SEHAT DI DESA SUKOJEMBER KECAMATAN JELBUK JEMBER - SUTARMI SUTARMI (LPPM Universitas dr. Soebandi, 2026)
Pregnancy is a physiological process that requires the mother's physical and psychological preparation for a healthy and safe birth. Lack of physical activity during pregnancy can increase the risk of discomfort and complications during labor. One promotion and prevention initiative that can be implemented is community-based prenatal exercise. This community service activity aims to increase pregnant women's knowledge and participation in maintaining a healthy pregnancy through an innovative community-based prenatal exercise program in Sukojember village, Jelbuk district, Jember regency. The activity's methods include health education, prenatal exercise demonstrations, and practical exercises. The target group consisted of 15 pregnant women in their second and third trimesters. The evaluation was conducted through observation and a question-and-answer session before and after the activity. The results showed an increase in pregnant women's knowledge of the benefits of prenatal exercise and increased participation in health activities. Community-based prenatal exercise is an effective way to educate and empower the community to achieve healthy pregnancies. It is hoped that this activity can be continued regularly through collaboration with village midwives and health workers.